The social positions of Estonian educators before and during the COVID-19 pandemic - Jõgi, Larissa; Rannala, Ilona-Evelyn; Jüristo, Kristi (Adult Education Discourses, 2024)
The context of adult and youth education has become more diverse. The COVID-19 pandemic affected changes in practice and had a particular impact on the social positions of educators. This paper presents the findings from qualitative exploratory research that aims to explore and understand the social positions of educators. The paper presents key findings based on research questions: what are the social positions of educators before and during the COVID-19 in Estonia? This research applied the theoretical concept of positioning. Empirical data was collected in two stages using five focus groups and six individual semi-structured interviews with educators from non-formal learning settings. Data was analysed using thematic analysis and portrayal methods. Four positions and four interrelated modes of the social positions of educators were explored. Social positions appeared in educators’ values, beliefs, professional activities, dialogue, and reflections. The most valuable position for educators during the COVID-19 pandemic time was the position of being an equal partner which is the main basic interactive positioning mode for developing and maintaining social positions.